The Tropical managed Forests Observatory: a research network addressing the future of tropical logged forests. Issue 1 (28th July 2014) - Sist, Plinio; Rutishauser, Ervan; Peña‐Claros, Marielos; Shenkin, Alexander; Hérault, Bruno; Blanc, Lilian; Baraloto, Christopher; Baya, Fidèle; Benedet, Fabrice; da Silva, Katia Emidio; Descroix, Laurent; Ferreira, Joice Nunes; et al.
Abstract While attention on logging in the tropics has been increasing, studies on the long‐term effects of silviculture on forest dynamics and ecology remain scare and spatially limited. Indeed, most of our knowledge on tropical forests arises from studies carried out in undisturbed tropical forests. This bias is problematic given that logged and disturbed tropical forests are now covering a larger area than the so‐called primary forests. A new network of permanent sample plots in logged forests, the Tropical managed Forests Observatory (TmFO), aims to fill this gap by providing unprecedented opportunities to examine long‐term data on the resilience of logged tropical forests at regional and global scales. TmFO currently includes 24 experimental sites distributed across three tropical regions, with a total of 490 permanent plots and 921 ha of forest inventories.